THE ROLE OF GLOBALIZATION IN LEGAL REFORM IN INDONESIA - Trisnanti, Ines Lovitya; Amelia, Mays; Sushanty, Vera Rimbawani (jfpublisher, 2025)
Globalization has had a major impact on various aspects of life, including criminal law. In Indonesia, this has prompted the need for criminal law reform to respond to global challenges, such as the integration of international law, the development of information technology, and increased cooperation in law enforcement across countries. The aim of this research is to determine the impact of globalization on legal reform in Indonesia. This study uses a normative legal method with a descriptive approach to evaluate the influence of globalization on criminal law reform in Indonesia. The findings show that globalization affects regulation, legal implementation, and encourages harmonization of national law with international standards. Globalization also has an impact on regulations in the fields of investment, trade, and other economics, and raises challenges such as cybercrime and misuse of technology. This requires legal reform to be more adaptive and relevant. The development of information technology creates new challenges in the form of digital crimes that have not been adequately regulated in national law. Therefore, legal reform is needed to accommodate these developments and maintain the effectiveness of the legal system. This study emphasizes the importance of synchronizing national law with global dynamics, without ignoring the local social and cultural context.